Serum Gamma-Glutamyltransferase Levels Predict Mortality in Patients With Peritoneal Dialysis. Issue 31 (August 2015) - Park, Woo-Yeong; Kim, Su-Hyun; Kim, Young Ok; Jin, Dong Chan; Song, Ho Chul; Choi, Euy Jin; Kim, Yong Lim; Kim, Yon Su; Kang, Shin Wook; Kim, Nam Ho; Yang, Chul Woo; Kim, Yong Kyun; et al.
<x xml:space="preserve">Abstract</x> Abstract Serum gamma-glutamyltransferase (GGT) level has been considered marker of oxidative stress as well as liver function. Serum GGT level has been reported to be associated with the mortality in hemodialysis patients. However, it is not well established whether serum GGT level is associated with all-cause mortality in peritoneal dialysis (PD) patients. The aim of this study was to determine the association between serum GGT levels and all-cause mortality in PD patients. PD patients were included from the Clinical Research Center registry for end-stage renal disease cohort, a multicenter prospective observational cohort study in Korea. Patients were categorized into 3 groups by tertile of serum GGT levels as follows: tertile 1, GGT < 16 IU/L; tertile 2, GGT = 16 to 27 IU/L; and tertile 3, GGT > 27 IU/L. Primary outcome was all-cause mortality. A total of 820 PD patients were included. The median follow-up period was 34 months. Kaplan–Meier analysis showed that the all-cause mortality rate was significantly different according to tertiles of GGT (P = 0.001, log-rank). The multivariate Cox regression analysis showed that higher tertiles significantly associated with higher risk for all-cause mortality (tertile 2: hazard ratio [HR] 2.08, 95% confidence interval [CI], 1.17–3.72, P = 0.013; tertile 3: HR 1.83, 95% CI, 1.04–3.22, P = 0.035) in using tertile 1 as the reference group after adjusting for clinical variables. Our study demonstrated that high serum GGT levels were an independent risk factor for all-cause mortality in PD patients. Our findings suggest that serum GGT levels might be a useful biomarker to predict all-cause mortality in PD patients.